Implementation of Assignment Method in Improving Teachers' Ability to Analyzing SK (Competency Standards) and KD (Basic Competencies) at SMPN 1 Tapung Hulu Kampar - Kresna, Pharada (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
This paper describes how the assignment method can improve teachers' abilities in analyzing SK and KD at SMPN 1 Tapung Hulu Kampar. Based on the description of the background, problem identification, and problem limitation, the focus of the research is related to the implementation of assignment methods to improve teachers' abilities in analyzing SK and KD at SMPN 1 Tapung Hulu Kampar. The research action hypothesis is